Protective factors against parental burnout during the COVID-19 pandemic - Yael Enav; Yaara Iron; Inbal Kivenson Bar-On; Miri Scharf (Scientific Reports)
Abstract The COVID-19 pandemic has negatively influenced families across the world and contributed to the likelihood of increased parental burnout and decreased parental psychological well-being. However, not all parents experienced parental burnout during the pandemic. In the current study, we focused on protective factors that buffered the negative effects of the COVID-19 pandemic on parents and supported parents’ quality of life. Based on previous literature, we hypothesized optimism, humor, and resilience will be associated with lower levels of parental burnout. Two hundred and eighty-one Israeli parents participated in the study, completing questionnaires during the government-mandated lockdown. Questionnaires examined information pertaining to both participants’ personal characteristics (optimism and pessimism, self-enhancing humor, resilience, parental stress, and perceptions of the youngest child’s functioning) and background characteristics (parental age, gender, health condition, socioeconomic status, employment status, and youngest child’s age) to examine the relationship between these variables and parental burnout. Findings indicate that resilience, optimism, and humor facilitated reduced parental burnout and enhanced parental well-being during the pandemic. However, these variables were not associated with parents’ stress perception. This study sheds light on the importance of having an optimistic perspective, positive sense of humor, and resilience at times of prolonged stress. Implications for interventions targeting optimistic attitudes and humor are suggested.